2019
DOI: 10.1038/s41598-019-42497-z
|View full text |Cite
|
Sign up to set email alerts
|

Impact of environmental factors on aquatic biodiversity in roadside stormwater ponds

Abstract: Constructed stormwater ponds mitigate runoff volumes and pollution, and provide other ecosystem services, such as supporting biodiversity, but these services attracted relatively less attention. The impacts of the pollution levels in the water column and sediments, the physical characteristics of ponds, and the presence of amphibians on the macroinvertebrate community composition and biodiversity were explored in twelve stormwater ponds in Norway. Also, the similarities between macroinvertebrate, zooplankton a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 48 publications
5
31
0
Order By: Relevance
“…The concentrations of PAHs in the sedimentation ponds in the present study are comparable with the highest concentrations found in other Norwegian sedimentation ponds 18,31 . It is also to some extent coherent with a Danish study 11 .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The concentrations of PAHs in the sedimentation ponds in the present study are comparable with the highest concentrations found in other Norwegian sedimentation ponds 18,31 . It is also to some extent coherent with a Danish study 11 .…”
Section: Discussionsupporting
confidence: 90%
“…Sedimentation ponds are built to mimic natural ponds and processes and these artificial ponds can be rapidly colonized by aquatic organisms 12,13 . Several recent studies have indicated that highway sedimentation ponds (and also other stormwater sedimentation ponds) are able to support and promote biodiversity at a local and regional scale 1418 , even specifically for odonatan diversity 19 . These studies underline the sedimentation ponds’ relevance in an ecological context, as they can act as steppingstones and secure connectivity throughout the surrounding landscape.…”
Section: Introductionmentioning
confidence: 99%
“…High submerged macrophyte cover was qualitatively observed in this waterbody during the field sampling. A strong positive relationship between zooplankton diversity and richness and macrophyte abundance has been shown in a few studies in other temporary and permanent ponds including stormwater detention structures (Mimouni et al 2018;Sun et al 2019). Possible macrophyte effects that could drive zooplankton species richness include ecological gradient such as food availability and low predator visibility (Mimouni et al 2018).…”
Section: Spatial and Temporal Variation Of Zooplankton Communitiesmentioning
confidence: 89%
“…Furthermore, a sharp decline in the biomass of the cladoceran group with an increase in TP was reported by Pinto-Coelho and Bezerra-Neto (2005). Sun et al (2019) showed that urban ponds that function as urban drainage systems or stormwater detention structures not only act as pollutant trap but also provide suitable habitats for pollution-tolerant taxa.…”
Section: Urbanization and Nutrient Gradient On Zooplankton Abundance mentioning
confidence: 99%
“…Therefore, the notion of water quality does not always coincide with such important parameters as species diversity (number of species) and biodiversity, e.g. under the β-mesosaprobic conditions, the diversity can significantly increase along with the resource base [Sun et al, 2019].…”
Section: Introductionmentioning
confidence: 99%